Compensation Strategies Used by EFL Learners in Speaking and Listening Skills - Sahib, Shehla Mohsin Abdul (University of Thi-Qar Journal, 2019)
This study aims to provide an empirical foundation for the students strategies to compensate for missing knowledge in listening and speaking skills during undertaking an oral exam interview. Observable compensation strategies that were employed and not employed in this paper written. In addition, strategies are ranked in order of most utilized to least utilized by study participants. Further correlation results of strategies to test score and strategies to the sex and age variables are examined. Relationships were observed between guessing strategies and female students, as well as guessing strategies and older students. Also students who engaged in reduction strategies such as giving up and replacement were most likely to have lower test scores, suggesting the importance of teaching them alternations to these strategies.